Microfossil census counts from a Holocene sediment core obtained southwest off the Cabo Verde archipelago (MUC5) - Irene Pérez-Rodríguez; Dirk Nürnberg; Julie Schindlbeck-Belo; Jack Wharton; Thor H Hansteen; Veerle A I Huvenne; David J R Thornalley; Ángela Mosquera Giménez; Steffen Kutterolf; Kelsey Archer Barnhill; Covadonga Orejas (PANGAEA, 2024)
This dataset provides absolute abundance data of planktonic foraminifera (identified at the species level), benthic foraminifera and radiolaria (both counted as total numbers). The microfossils were obtained from a sediment core collected at 4394 m water depth off the Cabo Verde archipelago which covers most of the Holocene Epoch. Counts were performed on the >150 μm sediment fraction, with a minimum of 300 planktonic foraminifera specimens per sample.